Impact of Corporate Governance on the Corporate Social Responsibility Disclosure: Empirical Evidence from Financial and Non-Financial Sectors of Pakistan: Impact of Corporate Governance on the Corporate Social Responsibility Disclosure in Pakistan - Bashir, Malik Fahim; Younas, 1. Omer; Rashid, Kashif (International Journal of Contemporary Economics and Administrative Sciences, 2023)
This study investigates the impact of corporate governance on corporate social responsibility (CSR) disclosure in financial and non-financial sectors of Pakistan from 2010-2016. The content analysis technique is used to report the CSR disclosure of the companies. The Reporting Frequency Comparison and Paired Sample T-Test are conducted to compare the CSR disclosure in both the sectors and determine the potential change in the CSR disclosure before and after introducing the Securities and Exchange Commission of Pakistan CSR voluntary Guidelines 2013. Furthermore, random effect regression highlights that the non-executive directors and foreign ownership significantly impact the CSR disclosure in the financial sector, while in the non-financial sector, only foreign directors are found to influence the CSR disclosure. Among all postulated hypotheses, only H1 & H4 are accepted in financial and non-financial sectors, with H2 only accepted in the financial sector. The Reporting Frequency Comparison and T-test results suggest that CSR disclosure is higher in the financial sector, and the level of CSR disclosure has increased significantly after introducing CSR voluntary Guidelines, 2013. This research study is novel and has set practical implications for the policymakers as it has performed reporting frequency-based comparison between both the sectors and has identified the various CSR sectors in which both financial & non-financial sectors may improve upon their social performance.